2018
DOI: 10.3390/e20100743
|View full text |Cite
|
Sign up to set email alerts
|

Maximum-Entropy Tools for Economic Fitness and Complexity

Abstract: The concepts of economic fitness and complexity, based on iterative and interdependent definitions of the quality of exporting countries and exported products, have led to novel insights into the dynamics of production and trade. A key step in the calculation of these quantities is the preliminary identification of statistically relevant country-product pairs.In this paper, we propose a method that could improve the current practice of filtering based on the revealed comparative advantage, by employing the max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The maximum entropy principle is extensively applied in many disciplines [ 28 , 29 , 30 , 31 , 32 ]. In information theory, if there is a discrete random variable, X , with possible values of { x1, x2, …, xn }, and probability mass function, P(X ), the entropy, H, of X is defined as follows: where E is the expectation operator, r is the logarithmic base, which generally takes a value of two [ 33 , 34 , 35 ] (in this study, r = 2).…”
Section: Methodsmentioning
confidence: 99%
“…The maximum entropy principle is extensively applied in many disciplines [ 28 , 29 , 30 , 31 , 32 ]. In information theory, if there is a discrete random variable, X , with possible values of { x1, x2, …, xn }, and probability mass function, P(X ), the entropy, H, of X is defined as follows: where E is the expectation operator, r is the logarithmic base, which generally takes a value of two [ 33 , 34 , 35 ] (in this study, r = 2).…”
Section: Methodsmentioning
confidence: 99%
“…The index introduced by Balassa, named Revealed Comparative Advantage (RCA) and extensively employed in the field of Economic Complexity [1][2][3][4]7], does not follow from any formal derivation, being simply deduced from a quite general rationale. In fact, it can be shown that Balassa's RCA is a comparison between the empirical value of a country-specific product export and its expected counterpart under a null-model preserving the total export of each country and the total export of each product [8][9][10]. It is also worth mentioning that the application of RCA has gone far beyond international trade, as it has been applied (sometimes with a different name) to analyze patenting data for technologies [11,12], employment data for sectoral studies [13] and scientific publication for science production [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Third, we overcome the intrinsic limitation of Balassa's recipe, which prescribes comparing an empirical value with its expected counterpart (as noticed in [10], an overall poor validation from a statistical point of view). Specifically, using the BiWCM's probability distributions, we calculate the p-value associated with each country-specific product export and perform a proper test of hypothesis.…”
Section: Introductionmentioning
confidence: 99%